2020
DOI: 10.5539/ibr.v13n9p55
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fair Value Accounting on Information Asymmetry: Evidence from Jordanian Banking Sector

Abstract: This study aims at examining the impact of Fair value accounting measured by other comprehensive income on information asymmetry measured by the bid-ask spread in the Jordanian banking sector between 2010 and 2017. The study sample consisted of the thirteen commercial banks listed in Amman Stock Exchange, and panel data analyses were employed to test the study hypothesis, data for the study was gathered through the annual financial reports disclosed on Amman Stock Exchange. The findings revealed that fair valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This assertion also implies the accuracy of ending balances in terms of impairment calculations, allowances, depreciation, amortization, and depletion, arriving at net realizable value and fair value. Manipulating account balances by exploiting flexibility in accounting policies and estimates is not only common but also has a serious impact on the validity of financial reporting (Lau, 2021;Altawalbeh, 2020;Ghazalat & AlHallaq, 2024;Ajekwe, 2021;Bajaja & Khalifa, 2015). Bajaja & Khalifa (2015) reported that the most commonly used methods of earnings management in Saudi Arabia are manipulation of allocations, asset valuation, and timing of revenue recognition.…”
Section: Survey Resultsmentioning
confidence: 99%
“…This assertion also implies the accuracy of ending balances in terms of impairment calculations, allowances, depreciation, amortization, and depletion, arriving at net realizable value and fair value. Manipulating account balances by exploiting flexibility in accounting policies and estimates is not only common but also has a serious impact on the validity of financial reporting (Lau, 2021;Altawalbeh, 2020;Ghazalat & AlHallaq, 2024;Ajekwe, 2021;Bajaja & Khalifa, 2015). Bajaja & Khalifa (2015) reported that the most commonly used methods of earnings management in Saudi Arabia are manipulation of allocations, asset valuation, and timing of revenue recognition.…”
Section: Survey Resultsmentioning
confidence: 99%
“…Rawaa and Imad [29] explored fair value's influence on the accounting system of an Iraqi economic unit revealing that the financial position and comprehensive income statements were prepared according to fair value accounting. Altawalbeh [30] investigated the impact of fair value accounting on information asymmetry in the Jordanian banking sector. Results indicated that fair value has a significant negative effect on information asymmetry enhancing stakeholder access to accurate and relevant information.…”
Section: Previous Studiesmentioning
confidence: 99%
“…A central explanation for the intervention is to provide useful information for the valuation of companies, consistent with the objectives of the Conceptual Framework for financial reporting than other measurement bases for both financial assets and liabilities (IASB, 2020; Kothari et al , 2010; Procházka, 2011). Palea and Maino (2013), Barth (2014) and Altawalbeh (2020) contend that fair value enhances the transparency of financial statements, which subsequently amplifies the value relevance of accounting information as users can value companies by discounting the markets’ future expected cash flows. In their literature review, Barth et al (2001) observe that the fair value measurement of financial assets and liabilities positively correlates with equity market value.…”
Section: Theory and Literature Reviewmentioning
confidence: 99%
“…Managers have been found to display intentional bias in their estimation when allowed to use discretion and highly subjective accounting information (Aboody et al, 2006). Level 3 fair values are subject to higher information asymmetry than Levels 1 and 2 fair values as their valuation derives from company-specific data and management's assumptions about market participants (Palea and Maino, 2013;Song et al, 2010;Altawalbeh, 2020). Investors typically place less importance on fair value measurements that they perceive to possess greater uncertainty (i.e.…”
Section: Hypotheses Developmentmentioning
confidence: 99%